Humanitarian Aid of the Red Cross and Other Public Organizations of the Netherlands To Soviet Russia During the Famine of 1921–1923 - G. G. Tsidenkov (Vestnik MGIMO-Universiteta)
Historiography of the famine in Soviet Russia and Ukraine 1921-23. includes a large number of scholar papers covering foreign humanitarian aid to starving population in the context of the work of such large organizations as the American Relief Administration, the Nansen Committee, etc. At the same time, there are practically no articles and thesis which fully describe the assistance to the Soviet starving from individual states and national aid committees. The purpose of this article is to highlight and summarize the main aspects of the activities of the Dutch charitable and public organizations on the territory of Soviet Russia and the Ukrainian SSR during the famine of 1921-23 on the basis of documents from the Russian central and regional archives, as well as the National Archives of Sweden, whose data are first introduced into the scientific circulation. Despite the absence of diplomatic relations between Soviet Russia and the Netherlands, representatives of almost all sectors of Dutch society took part in that activities. The collected data allow us to identify four main channels for the receipt of Dutch humanitarian aid in the areas affected by crop failure:1) Pro-government and public charitable organizations (the Red Cross of the Netherlands, the Dutch branch of the International Union "Save the Children"), which provided aid to the population in Volga region, Crimea and in Ukraine. In addition to sending humanitarian supplies, the Dutch Red Cross equipped its own expedition to Samara province;2) Associations of trade unions of the Second International, which participated in the financing of an independent expedition of the "International Federation of Trade Unions" to the Chuvash Autonomous Region;3) communist trade unions and associations of the Netherlands, acting through the organization "International Workers' Aid", which took part in the restoration of the Soviet national economy, and also maintained numerous orphanages in Soviet Russia;4) Religious societies of Dutch Mennonite Protestants, which sent humanitarian aid to the places of settlement of their co-religionists, where, at the insistence of the Soviet government, they provided aid to all those in need, regardless of religion.All the activities of various Dutch organizations and individual citizens in Soviet Russia and the Ukraine showed the readiness of the population and political forces of the Netherlands to maintain close contacts and interaction between our peoples, regardless of the official relations of states and political differences.